THE CONCEPT OF DEPRESSION ACCORDING TO SURAH MARYAM VERSES 23-26 : A STUDY OF COUNSELING AND SPIRITUAL PERSPECTIVES - Mustoha, Siti Hajar Binti (Jurnal Konseling Pendidikan Islam, 2025)
Depressive disorder is a disorder of emotional, emotional, and mental stress that is recognized globally. The population of depressive disorder is among the forms of mental disorders, especially if the majority of countries experience a change in norms after the pandemic phase that changes lifestyles. Forms of psychotherapy for depressive disorders have been organized with various disciplines, but therapy in this psychology is still widely controlled by the West. It turns out that psychological therapy recorded in the Qur'an is still not handled by the majority of counselors. Regarding this study, the study will focus on the description and concept of depressive disorders recorded in Surah Maryam verses 23 to 26. Furthermore, this study will explain how to overcome depression from a counseling and spiritual perspective based on Surah Maryam verses 23 to 26. The Qur'an and tafsir are the main sources of this research. This research is a type of library research with a qualitative method. The data from this study was obtained from the results of documentation and observation using data analysis, namely data reduction, data presentation, and verification. The results of the study show that mental disorders are not impossible to apply to humans who face stressful situations. This study concludes that a combination of counseling, spiritual, and physical elements can form a therapy that covers all aspects of human beings and helps depressed people get out of confusion and restore rationality in making choices in life. In conclusion, an approach in therapy to depression that includes psychological aspects can restore rationality and emotions, well-being from human physical nourishment, and spiritually guided peace of mind. And it turns out that in psychology Islam does not only focus on the spiritual aspect but emphasizes the psychological and physical aspects of human beings in achieving prosperity.